The betting line on beef: ex ante estimates of the benefits of research on improved pasture for the Latin American tropics - Seré, Carlos; Jarvis, Lovell S. (International Service for National Agricultural Research, 1990)
This paper estimates that the expected returns to improved pasture research (IPR) in the Latin American tropics are very high and suggests that current research in IPR is significantly underfunded. Although increased competition from poultry may reduce future regional beef consumption, regional beef consumption and production decisions can be divorced, provided that beef supluses can be exported.